Altered RIG‐I/DDX58‐mediated innate immunity in dermatomyositis. Issue 3 (29th April 2014) - Suárez‐Calvet, Xavier; Gallardo, Eduard; Nogales‐Gadea, Gisela; Querol, Luis; Navas, Miquel; Díaz‐Manera, Jordi; Rojas‐Garcia, Ricard; Illa, Isabel
Abstract We investigated the molecular mechanisms involved in the pathogenesis of three inflammatory myopathies, dermatomyositis (DM), polymyositis (PM) and inclusion body myositis (IBM). We performed microarray experiments† using microdissected pathological muscle fibres from 15 patients with these disorders and five controls. Differentially expressed candidate genes were validated by immunohistochemistry on muscle biopsies, and the altered pathways were analysed in human myotube cultures. Up‐regulation of genes involved in viral and nucleic acid recognition were found in the three myopathies but not in controls. In DM, retinoic acid‐inducible gene 1 (RIG‐I, DDX58) and the novel antiviral factor DDX60, which promotes RIG‐I‐mediated signalling, were significantly up‐regulated, followed by IFIH1 (MDA5) and TLR3. Immunohistochemistry confirmed over‐expression of RIG‐I in pathological muscle fibres in 5/5 DM, 0/5 PM and 0/5 IBM patients, and in 0/5 controls. Stimulation of human myotubes with a ligand of RIG‐I produced a significant secretion of interferon‐β (IFNβ; p < 0.05) and up‐regulation of class I MHC, RIG‐I and TLR3 (p < 0.05) by IFNβ‐dependent and TLR3‐independent mechanisms. RIG‐I‐mediated innate immunity, triggered by a viral or damage signal, plays a significant role in the pathogenesis of DM, but not in that of PM or IBM. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd